Needs analysis for developing a STEM-PBL-based student worksheet (LKPD) in physics learning on Newton's second law at the senior high school level - Juwita Priyanti; Erwina Oktavianty; Naim Sulaiman (Universitas PGRI Pontianak, 2026)
This study aims to analyze the needs for developing a STEM-PBL-based Student Worksheet (LKPD) on Newton's Second Law at the senior high school level. As the initial stage of a research and development process, the needs analysis provides a foundation for producing a modern and effective worksheet aligned with the demands of twenty-first-century learning. A survey method was employed, involving 125 grade XI students selected through purposive sampling, together with several physics teachers in Pontianak. Data were collected using a validated needs-analysis questionnaire distributed via Google Form. The results show that physics learning remained dominated by the lecture method and conventional media such as textbooks and PowerPoint, so that student engagement was not optimal. Nevertheless, most students had positive experiences with worksheets that helped them understand the material, and both students and teachers expressed strong interest in the STEM approach and the Problem-Based Learning (PBL) model, which were perceived as engaging, contextual, and supportive of critical thinking and problem-solving skills. These findings indicate that developing a STEM-PBL-based LKPD is needed as an instructional-material innovation appropriate to the demands of the twenty-first century.